2007
DOI: 10.1542/peds.2006-3108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol With Pentobarbital/Midazolam/Fentanyl Sedation for Magnetic Resonance Imaging of the Brain in Children

Abstract: Propofol permits faster onset and recovery than, and comparable efficacy to, a pentobarbital/midazolam/fentanyl regimen for sedation of children for MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 39 publications
5
46
0
2
Order By: Relevance
“…The conventional doses of Propofol used for induction and maintenance of sedation for paediatric MRI 2-6 mg/kg and 100-200 μgm/kg/min respectively. 9 These doses sometimes cause adverse effect like apnoea, injection site pain, involuntary movement and hypotension. 10 Tomatir et al reported that, use of small dose of Ketamine 0.5 mg/kg allows successful scan completion with lower induction and maintenance doses of propofol beside haemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional doses of Propofol used for induction and maintenance of sedation for paediatric MRI 2-6 mg/kg and 100-200 μgm/kg/min respectively. 9 These doses sometimes cause adverse effect like apnoea, injection site pain, involuntary movement and hypotension. 10 Tomatir et al reported that, use of small dose of Ketamine 0.5 mg/kg allows successful scan completion with lower induction and maintenance doses of propofol beside haemodynamic stability.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal delivery of sedation is accomplished by clinician strained in anesthesia. Their experience would allow them to identify and utilize the best available drugs and techniques to full potential to obtain the optimal outcome [6][7][8]10,12,15,19,20]. This would enhance patient safety and also result in studies yielding data with comparable methodologies, skills, and techniques.…”
Section: Proposal For Solutionmentioning
confidence: 99%
“…The Ramsay score 21has been recommended; itis a well-known and frequently applied scoring system, used for documentation of adequate depth of sedation [7,13,20,22].…”
Section: Proposal For Solutionmentioning
confidence: 99%
“…There was no evidence of hypoperfusion in the subjects who experienced propofol-induced hypotension by the aforementioned criteria, a fi nding that is consistent with previous studies. 5,34 The aforementioned physical signs are subjective measures, however, with signifi cant interrater variability, which reduces their reliability.…”
Section: Figurementioning
confidence: 99%